Cheese from milk powder - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
The National Dairy School in Mamirole, Doubs (France) has developed a simple and inexpensive procedure to transform milk powder into cheese and thus help to improve both the food and health situation in Third World countries. The procedure consists...